Effects of half-time re-warm-up with core strength exercises on subsequent agility and power performance in basketball players - Yang, Y.-R.; Chen, C.; Pan, C.-H.; Yen, S.-Y.; Cheng, C.-F. (The Journal of Strength and Conditioning Research, 2025)
This study investigated the effects of half-time re-warm-up (RW) comprising core strength exercise (CSE) on basketball players' subsequent power and change of direction (COD) performance. Twelve male collegiate basketball players were recruited to perform 3 conditions--CSE RW on a stable platform (STA) or an unstable platform (USTA) and passive rest (control, CON)--in randomized, counter-balanced order after a modified Loughborough intermittent shuttle test (LIST). The COD and power performance tests were administered before the LIST and after the interventions. Heart rate (HR) was continuously measured during each trial. Results showed significantly lower changes in T-test time in STA compared with CON (p < 0.05). Changes in countermovement jump height in STA were significantly higher than those in CON (p < 0.05). During the isometric midthigh pull test, changes in the maximum rate of force development (RFD) (p < 0.05), RFD in the range of 0-90 milliseconds (p < 0.05), 0-150 milliseconds (p < 0.05), 0-200 milliseconds (p < 0.05), and 0-250 milliseconds (p < 0.05), in STA were significantly higher than those in CON. In addition, RFD in the range of 0-150 milliseconds (p < 0.05) and 0-250 milliseconds (p < 0.05) in USTA was significantly higher than that in CON. The mean HR during USTA was significantly higher than that in STA and CON (p < 0.05). These findings indicated that CSE RW during halftime might prevent power and COD performance decline in the second half of a game, with practical implications for coaches and players.